On Complete Convergence in Marcinkiewicz-Zygmund Type SLLN for END Random Variables and its Applications - Ji Gao Yan (Humboldt-Universität zu Berlin, International Research Training Group 1792 "High Dimensional Nonstationary Time Series", 2018)
In this paper, the complete convergence for maximal weighted sums of extended negatively dependent (END, for short) random variables is investigated. Some sucient conditions for the complete convergence and some applications to a nonparametric model are provided. The results obtained in the paper generalise and improve the corresponding ones of Wang el al. (2014b) and Shen, Xue, and Wang (2017).
Keywords: C00; 330; Complete convergence; Maximal weighted sums; Extended negatively dependent